Factors Influencing Willingness to Pay for Covid-19 Vaccination - Bejranonda, Somskaow; Lim, Aunkung; Pipoblabanan, Chayun (Journal of Applied Economics and Management Strategy, 2023)
The outbreak of the coronavirus disease (COVID-19) around the world including Thailand has greatly affected the health and quality of life of people. This research would like to find out the factors influencing the willingness to pay of the people for the vaccination in order to prevent the COVID-19. The data was collected by online questionnaire, during March 2021, prior to the third wave of COVID-19 emergence in Thailand. The sample was 693 Thai people, aged from 18 years and over, living in Thailand. According to the Tobit Regression Analysis, at a statistical confidence level of 90%, the factors positively influencing willingness to pay of the people for the COVID-19 vaccination included awareness about changing lifestyle under COVID-19 pandemic, family/self-experience of getting COVID-19, knowledge and understanding about COVID-19, confidence in effectiveness of the vaccine, demand for vaccination, gender, education, income, having health insurance, and living in a strict controlled area. While the negative factor was having patients with chronic non-communicable disease in the family.